Strategies for the production of high-content fructo-oligosaccharides through the removal of small saccharides by co-culture or successive fermentation with yeast. (20th January 2016) - Nobre, C.; Castro, C.C.; Hantson, A.-L.; Teixeira, J.A.; De Weireld, G.; Rodrigues, L.R.
Highlights: Aureobasidium pullulans was used to produce fructo-oligosaccharides (FOS) mixtures. Saccharomyces cerevisiae ferments the residual sugars present in those FOS mixtures. Co-culture and two-step fermentations were used to produce enriched FOS samples. Two-step fermentations provided the highest yield (0.63 gFOS gSucrose −1 ) and purity (81.8%) of FOS. Residual sucrose was greatly reduced favouring the following FOS purification steps. Abstract: Fructo-oligosaccharides (FOS) obtained by fermentation of sucrose may be purified at large-scale by continuous chromatography (Simulated Moving Bed: SMB). In order to improve the efficiency of the subsequent SMB purification, the optimization of the fermentative broth composition in salts and sugars was investigated. Fermentations conducted at reduced amount of salts, using Aureobasidium pullulans whole cells, yielded 0.63 ± 0.03 g of FOS per gram of initial sucrose. Additionally, a microbial treatment was proposed to reduce the amount of small saccharides in the mixture. Two approaches were evaluated, namely a co-culture of A. pullulans with Saccharomyces cerevisiae ; and a two-step fermentation in which FOS were first synthesized by A. pullulans and then the small saccharides were metabolized by S. cerevisiae . Assays were performed in 100 mL shaken flasks and further scaled-up to a 3 L working volume bioreactor. Fermentations in two-step were found to be more efficient than the co-culture ones. FOS were obtained with a purity of 81.6 ± 0.8% (w/w), on a dry weight basis, after the second-step fermentation with S. cerevisiae . The sucrose amount was reduced from 13.5 to 5.4% in total sugars, which suggests that FOS from this culture broth will be more efficiently separated by SMB.